Long-term effects on cardiorespiratory and behavioral responses in male and female rats prenatally exposed to cannabinoid - Patrone, Luis Gustavo A. [UNESP]; Frias, Alana T. [UNESP]; Fantinatti, Gabriel T. [UNESP]; Stabile, Angelita M.; Klein, Wilfried; Bícego, Kênia C. [UNESP]; Gargaglioni, Luciane H. [UNESP] (American Physiological Society, 2024)
Development of the respiratory system can be affected by the use of drugs during pregnancy, as the prenatal phase is highly sensitive to pharmacological interventions, resulting in long-term consequences. The deleterious effects of external cannabinoids during gestation may be related to negative interference in central nervous system formation, cardiorespiratory system function, and behavioral disorders. Nevertheless, the impact of external cannabinoids on cardiorespiratory network development, chemosensitivity, and its future consequences in adulthood is still unclear. We evaluated the effects of prenatal exposure to a synthetic cannabinoid (WIN 55,212-2, 0.5 mg·kg-1·day-1) on the cardiorespiratory control and panic-like behavior of male and female rats in adulthood. Exogenous cannabinoid exposure during pregnancy resulted in a sex-dependent difference in breathing control. Specifically, males showed increased chemosensitivity to CO2 and O2, whereas females exhibited decreased sensitivity. Altered cardiovascular control was evident, with prenatally treated males and females being more susceptible to hypertension and tachycardia under adverse environmental conditions. Moreover, WIN-treated males exhibited higher fragmentation of sleep episodes, whereas females displayed anxiolytic and panicolytic behavioral responses to CO2. However, no changes were observed in the mechanical component of the respiratory system, and there were no neuroanatomical alterations, such as changes in the expression of CB1 receptors in the brainstem or in the quantification of catecholaminergic and serotonergic neurons. These findings highlight that external interference in cannabinoid signaling during fetal development causes sex-specific, long-lasting effects for the cardiorespiratory system and behavioral responses in adulthood.
Keywords: adulthood; brainstem; CB1 receptor; chemosensitivity; WIN 55,212-2